PENYUSUNAN LAPORAN KEUANGAN ORGANISASI NIRLABA BERDASARKAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NOMOR 45 (Studi Pada Masjid Al-Iman Bukit Tinggi) - Muhammad Rizqi, Reza; Nurfadliyah (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
This study aims to compile the financial statements of the Samsul Hidayah Mosque Moyo Village in accordance with the standards made by the Indonesian Accountants Association (IAI) namely Statement of Financial Accounting Standards (PSAK) No. 45. In this study, the authors analyzed the financial statements of the Samsul Hidayah Mosque with how to collect data, present data, analyze data, so as to produce conclusions about the actual picture, then compare with Statement of Financial Accounting Standards (PSAK) No.45. this type of research is qualitative with interpretive approach. The author uses data collection techniques through observation, interviews, and documentation to obtain relevant data. The results of this study indicate that the financial report of Al-Iman Bukit Tinggi Mosque is only a simple record of cash receipts and cash disbursements and the final balance of the mosque. However, the mosque management did not make an inventory of the assets owned by the mosque. The financial statements of Al-Iman Bukit Tinggi Mosque are not in accordance with the Statement of Financial Accounting Standards (PSAK) No.45 which consists of Financial Position Reports, Activity Reports, Cash Flow Statements, and Notes to Financial Statements